Long-term results of adjuvant intravesical chemotherapy with titanium glycerosolvate aquacomplex in patients with high risk nonmuscle-invasive bladder cancer - A. V. Zamyatin (Onkourologiâ, 2019)
The study objective is to evaluate the results of adjuvant intravesical chemotherapy (IVCT) using an original penetrant titanium glycerosolvate aquacomplex (TGA) compared to the standard technique of chemotherapy drug instillation in patients with high risk non-muscle-invasive bladder cancer.Materials and methods. The prospective study included 110 patients with non-muscle invasive bladder cancer. The treatment group (n = 55) included patients with high risk non-muscle-invasive bladder cancer who received a 6 week course of adjuvant IVCT with TGA; the control group (n = 55) included patients with high and intermediate risk non-muscle-invasive cancer who received a 6 week course of IVCT using the standard instillation technique: with chemotherapy drugs diluted in 0.9 % NaCl saline. Comparison of the effectiveness of the two techniques of adjuvant IVCT was performed using recurrence-free survival, progression and side effect rates. Significance was stated at p <0.05.Results. Median follow-up duration in the treatment group was 58 months, in the control group — 50 months (p >0.05). Disease progression was observed in 1 (1.8 %) patient in the treatment group and in 3 (5.4 %) patients in the control group (p >0.05). Median recurrence-free survival in the treatment group wasn’t reached, in the control group it was 52 months. Five-year recurrence free survival in the treatment group was 17 % higher than in the control group (64.9 % vs 47.9 %; p = 0.068). Despite the absence of significant differences between recurrence-free survival in the compared groups, a tendency toward its increase is observed in the treatment group after 12 months (p = 0.079). Side effects observed for the two instillation methods were toxicity grade I—II.Conclusion. Use of compositions of chemotherapy drugs with TGA as adjuvant IVCT allowed to improve the results of treatment of high risk non-muscle-invasive bladder cancer compared to the standard technique of instillation of chemotherapy drugs.